Drug-Related Problems in Tuberculosis Inpatients: Clinical Relevance and Influence on Hospital Stay Duration - Asniar Pascayantri; Fadhliyah Malik; Putri Juanti (Jurusan Farmasi Fakultas Kedokteran Universitas Lampung, 2026)
Pulmonary tuberculosis ranks as the second most widespread infectious disease worldwide and is caused by Mycobacterium tuberculosis. Its treatment requires the use of multiple medications, especially for inpatients and individuals with comorbidities. The greater the number of drugs used, the higher the likelihood of experiencing Drug-Related Problems (DRPs) throughout the treatment process. This study was conducted to examine the DRPs among pulmonary tuberculosis inpatients at RSUD Kota Kendari in 2023. This study employed a retrospective observational design with a descriptive-analytic approach. Study population consisted of all patients diagnosed with pulmonary tuberculosis who were admitted to RSUD Kota Kendari during the study period. The sample was selected using a total sampling technique, including all patients who met the inclusion and exclusion criteria. DRPs identification followed the guidelines of the PCNE version 9.00. From a clinical standpoint, results showed most frequent comorbidity was type 2 diabetes mellitus, and the most common coexisting condition was dyspnea. Regarding pharmacological treatment, 71.6% of patients received first-line anti-TB drugs during the intensive phase, 6.4% were in the continuation phase, and 22.0% were administered the second-line drug, levofloxacin. The most common DRPs were found in domain C1.4 (inappropriate drug combinations) at 94.6%, followed by domain P1.3 (untreated indications) at 2.2%, domain C1.6 (therapy not provided or incomplete despite indication) at 2.2%, and domain P2.1 (potential adverse drug reactions) at 1.1%. The chi-square test indicated no significant correlation between therapeutic outcomes and DRPs (p = 0.169); however, a significant relationship was observed between the length of hospital stay and DRP occurrence (p = 0.00). These findings underscore the importance of pharmacotherapy monitoring and interdisciplinary collaboration to minimize DRPs, especially in patients receiving complex tuberculosis treatment regimens.